Peritoneal adhesion prevention with a biodegradable and injectable N,O-carboxymethyl chitosan-aldehyde hyaluronic acid hydrogel in a rat repeated-injury model - Song, Linjiang (Sci Rep, 2016)
Postoperative peritoneal adhesion is one of the serious issues because it induces severe clinical disorders. In this study, we prepared biodegradable and injectable hydrogel composed of N,O-carboxymethyl chitosan (NOCC) and aldehyde hyaluronic acid (AHA), and assessed its anti-adhesion effect in a rigorous and severe recurrent adhesion model which is closer to clinical conditions. The flexible hydrogel, which gelated in 66 seconds at 37 °C, was cross-linked by the schiff base derived from the amino groups of NOCC and aldehyde groups in AHA. In vitro cytotoxicity test showed the hydrogel was non-toxic. In vitro and in vivo degradation examinations demonstrated the biodegradable and biocompatibility properties of the hydrogel. The hydrogel discs could prevent the invasion of fibroblasts, whereas fibroblasts encapsulated in the porous 3-dimensional hydrogels could grow and proliferate well. Furthermore, the hydrogel was applied to evaluate the anti-adhesion efficacy in a more rigorous recurrent adhesion model. Compared with normal saline group and commercial hyaluronic acid (HA) hydrogel, the NOCC-AHA hydrogel exhibited significant reduction of peritoneal adhesion. Compared to control group, the blood and abdominal lavage level of tPA was increased in NOCC-AHA hydrogel group. These findings suggested that NOCC-AHA hydrogel had a great potential to serve as an anti-adhesion candidate.